The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep21093
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase participates in the downregulation of T cell functions due to suppressor macrophages

Abstract: The cell-to-cell contact of T lymphocytes with immunosuppressive macrophages causes marked changes in the tyrosine phosphorylation of some cytosolic proteins of T cells. By phosphoproteome analysis, we identified a 36-kDa protein as aldose reductase (AR). The AR expression in T cells was not changed by TCR stimulation or due to cell-to-cell transmission of suppressor signals from immunosuppressive macrophages. Therefore, AR phosphorylation/dephosphorylation is essential for the transduction of TCR-mediated T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The current consensus is that ferroelectriclike switching in hafnia-based ferroelectrics does exist, but its origin still highly debated. Only one or two reports have shown a ferroelectric phase transition in this material (9,10). In addition, switching requires large applied fields and does not seem to proceed as in other ferroelectrics throufh movement of domain walls (11).…”
Section: A Key Piece Of the Ferroelectric Hafnia Puzzlementioning
confidence: 82%
“…The current consensus is that ferroelectriclike switching in hafnia-based ferroelectrics does exist, but its origin still highly debated. Only one or two reports have shown a ferroelectric phase transition in this material (9,10). In addition, switching requires large applied fields and does not seem to proceed as in other ferroelectrics throufh movement of domain walls (11).…”
Section: A Key Piece Of the Ferroelectric Hafnia Puzzlementioning
confidence: 82%
“…Previous work with other human AKRs showed recombinant proteins expressed in E. coli had up to 20 fold lower activity compared to native enzymes purified from human livers (Martin et al, 2006). Furthermore, some AKR family members require post-translational modifications for their cellular activities (Shimizu et al, 2016), so it possible that AKR1C1 expressed in E. coli lacked the necessary modifications for c-di-AMP binding.…”
Section: Discussionmentioning
confidence: 99%
“…Second, AR actions independent of its enzymatic activity were revealed in a study by Shimizu et al (140). Using phosphoproteome analysis and molecular studies, they showed that AR phosphorylation/dephosphorylation is essential for the transduction of T cell receptor-mediated T-cell stimulatory signals.…”
Section: Ar and Its Physiological Rolementioning
confidence: 99%
“…Importantly, upregulation of ERK1/2-mediated signaling pathways in T lymphocytes was linked to AR phosphorylation driven events. Shimizu et al ( 140 ) concluded that AR mediates intracellular transmission of the suppressor signal of immunosuppressive macrophages toward downstream ERK1/2 pathways, possibly through its direct interaction with acceptor proteins.…”
Section: Ar and Its Physiological Rolementioning
confidence: 99%